2012
DOI: 10.1109/tuffc.2012.2480
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modeling of a sandwiched plate piezoelectric transformer-based acoustic-electric transmission channel

Abstract: The linear propagation of electromagnetic and dilatational waves through a sandwiched plate piezoelectric transformer (SPPT)-based acoustic-electric transmission channel is modeled using the transfer matrix method with mixed-domain two-port ABCD parameters. This SPPT structure is of great interest because it has been explored in recent years as a mechanism for wireless transmission of electrical signals through solid metallic barriers using ultrasound. The model we present is developed to allow for accurate ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…These works, initiated in the United States by Saulnier in 2006 [19], gained interest in the navy due to the possibility of sending energy and information through the thick walls of submarines. Particularly significant results were published in the dissertation of Lawry [20] and in a dozen or so publications after its defense, e.g., [21,22]. The last two indicate that the state of knowledge allows the use of such relays on submarines today.…”
Section: Wireless Energy and Information Transfer Through Energy Harvmentioning
confidence: 99%
“…These works, initiated in the United States by Saulnier in 2006 [19], gained interest in the navy due to the possibility of sending energy and information through the thick walls of submarines. Particularly significant results were published in the dissertation of Lawry [20] and in a dozen or so publications after its defense, e.g., [21,22]. The last two indicate that the state of knowledge allows the use of such relays on submarines today.…”
Section: Wireless Energy and Information Transfer Through Energy Harvmentioning
confidence: 99%
“…With the introduction of the OFDM, SC-FDE and MIMO-OFDM, the communication rate has been greatly improved. 3 Characteristic of the Acoustic-Electric Channel A common system for ultrasonic wireless communication through metal barriers has a sandwiched multi-layer composite structure, in which piezoelectric transducers are closely stuck at opposite positions, normal to both sides of a metal barrier [6,7,[12][13][14][15][16][17][18]26,. As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…At this point, the simulation analysis method can be used to study the channel characteristic. The commonly used simulation methods include the equivalent circuit method [23,42], ABCD parameter method [13,14,26], finite element method [9,10] and time domain finite difference method [32], which are introduced in more details and compared as follows.…”
Section: Introductionmentioning
confidence: 99%
“…This type of system is useful in low-rate telemetry applications. Dedicated data implementations of these systems [4][5][6] have been shown to be capable of high data-rate communications, with both implementations employing multicarrier transmission techniques to achieve over 15 Mbps data-rates, with predictions of much higher rates being possible. Conversely, for strictly power transmission, a system [7] composed of disk transducers across a thick stainless steel barrier was shown to be capable of delivering at least 140 W with an approximate efficiency of 67 percent at 1.25 MHz; whereas Bao et al [8] demonstrated delivery of over 1 kW at 24.5 kHz with an efficiency of 84 percent while using highly specialized piezoelectric transducer stacks operating on a thin titanium barrier.…”
Section: Introductionmentioning
confidence: 99%
“…A similar type of model has been described by Lawry et al [18], which approached modeling of the channel's individual layers by isolating each layer and then modeling them using force-voltage mechanical analog ABCD-parameters, commonly known as acoustic transfer matrices, which map the pressure and particle velocities to adjacent interfaces. The modeling presented within this paper considers the independently traveling forward and reverse pressure waves as the mapped variables, which allows for a more intuitive understanding of the power flow characteristics of such systems.…”
Section: Introductionmentioning
confidence: 99%